The Nexuses between Community Attachment, Tourism Support, and Cultural Heritage Protection in the Bektashi Faith Destination: The Roles of Perceived Tourism Impacts and Residency Length - Şehnaz Demirkol; Senay Boz; Hatice Çifçi (Journal of Economy Culture and Society)
This study examines the nexus between community attachment (CA), residents’ perceived positive tourism impacts (POSI), residents’ perceived negative tourism impacts (NEGA), and their attitudes toward support for tourism development (SUPT) and protection of cultural heritage (SUPCH) in the Bektashi faith destination with the moderating role of length of residency. Using a quantitative research approach through the questionnaire technique, 245 eligible questionnaires were analyzed by partial least squares structural equation modeling (PLS-SEM). Findings confirmed the positive relationships among CA, SUPT, and SUPCH. However, only SUPCH positively mediated the relationship between CA and SUPT. Finally, length of residency (LOR) significantly moderated some relationships (i.e., CA and SUPCH; CA and POSI, NEGA and SUPT; and SUPCH and SUPT. Theoretically, this research concluded that CA and LOR are essential determinants of residents’ SUPT and SUPCH. Practically, policymakers and practitioners of faith destinations can develop strategies and take practical future actions.